Attachment’s Impact on the “Day Care” Children Initiative and Creativity in Bandung - Rahman, Syahnur; Dhycohianessa, Eries; Kosasih, Engkos; Irani , Yuni (International Journal of Psychosocial Rehabilitation, 2020)
Childhood is a period that has been disjointed from the period of dependence as a baby and becomes more independent. At this time the part of parents is very influential in the development of initiative and creativity of children. The aim of this study was to investigate the attachment impact on the “Day Care” children initiative and creativity in Bandung. This study has already activated to 40 children of day care (their ages were among about 3-5 years-old) based on sampling quota. The research method was a quantitative method with a questionnaire and scale instrument as the instruments. The data analysis was used Spearman correlation and multiple regression analysis. Based on the investigations, the conclusion submitted there is influence attachment to the initiative and creativity of children. The attachment has a greater influence on initiative compared to the creativity of day care children in Bandung.